Crop weather relationship in oilseed rape (Brassica napus) for north-west foothills of Himalayas, India - BHAGAT, RAKSHIT; SINGH, MAHENDER; SHARMA, B C (The Indian Journal of Agricultural Sciences, 2023)
Agrometeorological indices have a strong correlation with growth, yield attributes and yield of crop and can be effectively used to select suitable cultivar for specific environmental conditions. Therefore, to study the cumulative effect of weather variables in terms of agrometeorological indices on cultivars of oilseed rape (Brassica napus L.) sown under different sowing environments, field experiments were conducted at the research farm of Agrometeorology section, Sher-e-Kashmir University of Agricultural Sciences and Technology, Jammu, Jammu and Kashmir during winter (rabi) season of 2018–19 and 2019–20. The treatments were comprised of 3 sowing environments, viz. 42nd SMW (standard meteorological week), 44th SMW and 46th SMW along with 3 cultivars (GSL-1, ONK-1 and DGS-1) of oilseed rape in factorial randomized block design with 3 replications. The pooled data of 2 years revealed that all the cultivars of oilseed rape sown in 42nd SMW accumulated higher growing degree days (GDD), photothermal units (PTU) and heliothermal units (HTU) with higher rate of dry matter accumulation in comparison to 44th SMW and 46th SMW sown crop. The agrometeorological indices, viz. GDD, PTU and HTU were significantly positively correlated with growth parameters, yield attributes and yield at vegetative stage, while, PTU and HTU were negatively correlated at reproductive stage of the crop. Due to the significant impact of weather variables, the seed yield of all the oilseed rape cultivars decreased when the sowing was delayed from 42nd SMW to 46th SMW during both the years. Among cultivars, GSL-1 recorded significantly higher seed yield followed by ONK-1 and DGS-1.